PERENCANAAN SISTEM PENYEDIAAN AIR BERSIH PDAM KOTA SALATIGA - Agus Priyanto; Suripin Suripin; Salamun Salamun (Jurnal Karya Teknik Sipil, 2013)
The planning of the drinking water network system to maximize the utilization of available water resources. It necessary to planned in Argomulyo Sub-District is with the population projections, the number of public facilities that are available, and water demand from 2011 to 2021. After water demand are known then can be designed water piping network system by adjusting the state service area and topography analysis with EPANET 2.0 Simulation. EPANET 2.0.